Mariadahl, Pottawatomie County - Butler, Ursula (Kansas State University, The Chapman Center for Rural Studies, 2010)
Mariadahl, named after the Swedish founder's mother, meaning "Valley of Mary" grew on the cornerstone of the Swedish Lutheran church that called parishers to worship every Sunday by the sound of its beautiful bell.
Ursula Butler, “Mariadahl, Pottawatomie County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/34.
Keywords: Blue Valley; Mariadahl; Olsburg; Pottawatomie County; Sweden; Tuttle Creek Dam